The Influence of Organizational Culture, Leadership Style, and Discipline on Employee Performance at PT. Reads Media Indonesia - Mustapa, Zainuddin (Indonesian Journal Of Economy Studies, 2025)
This study aims to analyze the influence of organizational culture, leadership style, and discipline on employee performance at PT. Reads Media Indonesia. The research employed a quantitative method with a survey approach by distributing questionnaires to company employees as respondents. The collected data were analyzed using multiple linear regression tests to determine both the partial and simultaneous effects among the variables.The findings indicate that, partially, organizational culture, leadership style, and discipline have a significant effect on employee performance. Simultaneously, these three variables also show a significant influence on performance improvement. Among the variables examined, organizational culture has the most dominant effect in driving employee performance. These results affirm that a strong organizational culture, effective leadership, and good work discipline can create a conducive work climate that fosters productivity and the achievement of organizational goals.The implication of this research is that the management of PT. Reads Media Indonesia needs to strengthen a positive work culture, implement participative and performance-based leadership, and enforce discipline consistently in order to sustainably improve employee performance.